Investigation of oxidative potential of mahasudarshan churna using goat liver as in-vitro experimental model - Pandit, Bibhas; Satapathy, Trilochan; Bahadur, Sanjib; Dewangan, Jyoti (Journal of Applied Pharmaceutical Research, 2019)
The American Medical Research Community sounded a heavy metal warning against some herbo-mineral Ayurvedic formulations from Indian System of Medicine sold in United States of America. The products were rejected by Unites States Food and Drug Administration due to the presence of high level of lead, mercury and arsenic as impurities, marked as toxicity inducers. This work has been design to investigate whether the toxicity produced by Mahasudarshan churna is due to the results of lipid peroxidation, as oxidative degradation of phospholipids is one of the causes of drug-induced toxicity. The level of malondialdehyde, reduced glutathione and nitric oxide were estimated in control, drug-treated, drug-antioxidant treated and only antioxidant-treated group at two hours and six hours of incubation time in goat liver homogenates. Ascorbic acid was used to compare the oxidative potentials of Mahasudarshan churna. The level of malondialdehyde was found to be decreased in the drug-treated, drug-antioxidant treated and only antioxidant treated group where as the level of reduced glutathione and nitric oxide increased when compared to control. Above all the Drug-antioxidant treated group showed maximum anti-oxidant properties when compared to other groups. The study was designed to investigate the lipid peroxidation induction capacity of Mahasudarshan churna as consequences of its toxicity and found that lipid peroxidation is not the contributing factor